Q. 1 C4.3( 13 Votes )

# In the following,

Answer :

As, p + q = 2

⇒p = 2–q

putting the value of q in other equation,

⇒ pq = –24

⇒ (2–q)q = –24

⇒2q–q^{2} = –24

⇒q^{2}–2q–24 = 0

⇒q^{2}–6q + 4q–24 = 0

⇒q(q–6) + 4(q–6) = 0

⇒ (q + 4)(q–6) = 0

so, q = –4 & q = 6

as, p = 2–4

thus, p = 2 + 4 & p = 2–6

p = 6 & p = –4

Rate this question :

Factorise:

</pKarnataka Board - Mathematics Part I

Factorise:

</pKarnataka Board - Mathematics Part I

Factorise:

</pKarnataka Board - Mathematics Part I

In the following,Karnataka Board - Mathematics Part I

In the following,Karnataka Board - Mathematics Part I

In the following,Karnataka Board - Mathematics Part I

In the following,Karnataka Board - Mathematics Part I

Factorise:

</pKarnataka Board - Mathematics Part I

Factorise:

</pKarnataka Board - Mathematics Part I

Factorise:

</pKarnataka Board - Mathematics Part I